You need to notice first that you may convert the product `(z+1)(z-1)` into a difference of squares such that:

`(z+1)(z-1) = z^2 - 1`

Hence, you may write the transformed form of the equation of the function such that:

`w(z) = (z^2 - 1)(z^2+ 1)`

You need to convert again the product into a difference of squares such that:

`w(z) = z^4 - 1`

You need to differentiate the function with respect to z such that:

`w'(z) = 4z^3 - 0`

`w'(z) = 4z^3`

You need to find the second order derivative, hence, you need to differentiate w'(z) with respect to z such that:

`w''(z) = (4z^3)' => w''(z) = 12z^2`

**Hence, evaluating the first order derivative and the second order
derivative of function yields `w'(z) = 4z^3` and `w''(z) =
12z^2` .**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.